Pain kept under wraps of myelin sheath - Shubayev, Veronica I. (Frontiers in Pain Research, 2025)
The myelin sheath serves both as insulator and metabolic powerhouse for large-diameter dorsal root ganglia (DRG) neurons—some of the longest cells in the body—transmitting sensory impulses from the periphery to the spinal cord. When myelin is damaged, bioactive fragments of myelin basic protein (MBP) are released, playing a pivotal role in pathological pain. MBP-derived peptides (MBPd) emerge as a ubiquitous yet sex-specific mediator of pain. In females, MBPd triggers a widespread transcriptional response across the peripheral nerve, DRG, and spinal cord, leading to persistent, treatment-resistant tactile allodynia—pain from normally innocuous touch. In contrast, males exhibit only a localized transcriptional response, confined to the nerve, which does not extend to the DRG or spinal cord or induce pain. The sex difference is driven by MBPd's interaction with lipids and regulation of nuclear receptor transcription factors, including the estrogen receptor (ESR) and the liver X receptor (LXR)/retinoid × receptor (RXR) complex—key regulators of lipid and cholesterol metabolisms mounting sex-dependent immunity. By unraveling these fundamental mechanisms of myelin remodeling, this work opens the door to innovative, non-addictive, personalized therapeutics and diagnostics for chronic pain.